Ethics and the accounting profession in Malaysia / Muhammad Adam Bakar, Maisarah Mohamed Saat and Ainun Hj. Abdul Majid - Bakar, Muhammad Adam; Mohamed Saat, Maisarah; Abdul Majid, Ainun (Faculty of Accountancy, 2003)
Ethics, of late, had aroused significant interest amongst practitioners and academics alike. The collapse of Enron, the largest energy-trading company in the US had jolted the profession out of its complacency and serves a warning that all is not well with the profession. It is under scrutiny! The message is clear, if accountants want to be relevant, they have to be more diligent and ethical.